Kafkaesque worlds in real time - Troscianko, E (Sage, 2010)
We read in a linear fashion, page by page, and we seem also to experience the world around us thus, moment by moment. But research on visual perception shows that perceptual experience is not pictorially representational: it does not consist in a linear, cumulative, totalizing process of building up a stream of internal picture-like representations. Current enactive, or sensorimotor, theories describe vision and imagination as operating through interactive potentiality. Kafka’s texts, which evoke perception as non-pictorial, provide scope for investigating the close links between vision and imagination in the context of the reading of fiction. Kafka taps into the fundamental perceptual processes by which we experience external and imagined worlds, by evoking fictional worlds through the characters’ perceptual enaction of them. The temporality of Kafka’s narratives draws us in by making concessions to how we habitually create ‘proper’, linear narratives out of experience, as reflected in traditional Realist narratives. However, Kafka also unsettles these processes of narrativization, showing their inadequacies and superfluities. Kafka’s works engage the reader’s imagination so powerfully because they correspond to the truth of perceptual experience, rather than merely to the fictions we conventionally make of it. Yet these texts also unsettle because we are unused to thinking of the real world as being just how these truly realistic, Kafkaesque worlds are: inadmissible of a complete, linear narrative, because always emerging when looked for, just in time.